Effect of Feed Additives on Productivity and Campylobacter spp. Loads in Broilers Reared under Free Range Conditions - Guyard-Nicodème, Muriel; Huneau-Salaün, Adeline; Tatone, Fabrizio A.; Skiba, Fabien; Quentin, Maxime; Quesne, Ségolène; Poezevara, Typhaine; Chemaly, Marianne (Frontiers in Microbiology, 2017)
The poultry reservoir, especially broiler meat, is generally recognized as one of the most-important sources for human Campylobacteriosis. The measures to control Campylobacter targeted essentially the primary production level. The aim of this work was to evaluate the effectiveness of different treatments against natural Campylobacter colonization in a French experimental farm of free-range broilers during the whole rearing period. Five commercial products and a combination of two of them were tested and all the products were added to feed or to water at the dose recommended by the suppliers. Campylobacter loads in caeca and on carcasses of broilers at the slaughter were determined by culture methods. Natural contamination of the flock occurred at the end of the indoor rearing period between day 35 and day 42. At day 42, the multispecies probiotic added to the feed reduced the contamination of 0.55 log10 CFU/g (p=0.02) but was not significant (p> 0.05) at the end of rearing at day 78. However another treatment, a combination of a cation exchange clay-based product in feed and an organic acid mixture (formic acid, sodium formate, lactic acid, propionic acid) in water, led to a slight but significant reduction of 0.82 ± 0.25 log10 CFU/g (p= 0.02) compared to the control group at day 78. Testing this combination in field conditions in several flocks is needed to determine if it is biologically relevant and if it could be a valuable measure to reduce Campylobacter in broiler flocks.